Concepts of emotions in the english language from a cognitive-psychological perspective - Olga A. Kistanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the study of the characteristic features of cognitive psychology as a science of human interaction with the reality. The humans’ desire to gain some valuable things and their understanding of capabilities to implement this desire determine the occurrence of a certain emotion, prompting people to action. The cognitive content of the emotion of fear is a situation in which an individual predicts the probable damage and at the same time he hasn’t enough resources or ability to avoid this damage. The intensity of any emotion is determined by two factors: the amount of the predicted damage and the degree of its probability. The characteristic features of English linguacultural concepts of basic emotions are analyzed (the “fear” concept is taken as an example) and a typical scenario of a situation in which they arise is given.